ANALISIS PENGETAHUAN GIZI MAKANAN DAN POLA GAYA HIDUP PADA MAHASISWA - Ratmono, Bella Adik Ayu; Widodo, Achmad; Sholikhah, Anindya Mar'atus (Journal of Sport and Exercise Science, 2022)
Knowledge and good nutritional behavior will certainly affect the health of the body. However, students also need to pay attention to healthy lifestyles such as doing physical activity and improving sleep quality to avoid various diseases. The purpose of this study is to describe the knowledge of food nutrition and lifestyle patterns in students of Sports Science, Universitas Negeri Surabaya. It was a descriptive   quantitative research design with a survey method. A total of 30 students were taken using cluster random sampling. The research instrument used a questionnaire sourced from the Global Nutrition Knowledge Questionnaire (GNKQ), the International Physical Activity Questionnaire (IPAQ), and the Adolescents Sedentary Activity Questionnaire (ASAQ). Independent sample t-test was performed to compare the measured variables between male and female students. The results showed that most of the students 53.3%s had a good level of nutritional knowledge and the level of physical activity in the light category was 46.7%. Students are advised to limit their time on sedentary activities to 8 hours per day. Knowledge of food nutrition and healthy lifestyle patterns must be improved even though it is quite good, but it is necessary to improve the intensity of physical activity and sedentary lifestyle in order to have a positive impact on student health.